Risk factors influencing BRONJ staging in patients receiving intravenous bisphosphonates: a multivariate analysis. Issue 5 (May 2015) - Nisi, M.; La Ferla, F.; Karapetsa, D.; Gennai, S.; Miccoli, M.; Baggiani, A.; Graziani, F.; Gabriele, M.
Abstract The objective of this study was to determine, retrospectively, the influence of various risk factors on the staging of bisphosphonate-related osteonecrosis of the jaw (BRONJ) in a population attending a department of dentistry and oral surgery in Italy. Data were collected from the electronic and paper medical records of 90 patients receiving intravenous bisphosphonates. Two experienced and calibrated examiners used the American Association of Oral and Maxillofacial Surgeons updated 2009 classification to record the stage of BRONJ lesions. Multivariate ordinal logistic regression was performed to determine individual risk factors negatively affecting BRONJ staging. The factors associated with a worse BRONJ staging were high bisphosphonate cumulative dose (odds ratio (OR) 1.70, 95% confidence interval (CI) 1.02–2.82; P = 0.04), smoking (OR 1.80, 95% CI 1.03–2.80; P = 0.04), steroid intake (OR 1.70, 95% CI 1.00–2.87; P = 0.05), and a maxillary location of the lesion (OR 3.50, 95% CI 1.81–6.77; P < 0.01). Tooth extraction was the event that most negatively influenced BRONJ staging (OR 1.60, 95% CI 1.00–2.81; P = 0.05), in comparison to other events such as prosthetic trauma, implant treatment, oro-dental infection, and periodontal disease. Certain clinical and medical risk factors may determine a more severe staging of BRONJ lesions. Future studies are necessary to confirm these findings.